Affecting Factors for Implementing Performance-Based Maintenance Contracting: Perspective of Malaysian Road Contractors - R., Manogaran; Roshanida, A. Rahman; Azlina, Ismail; Intan Suhana, Mohd Razelan; P., Mandiartha (IOP Science, 2021)
Traditionally, road maintenance is conducted either using road authorities' in-house resources or method-based contracting, where contractors do the work and are paid based on predefined volume and unit prices. Nowadays, Performance-based Maintenance Contracting (PBMC) is one of the most current approaches in road maintenance works. PBMC provides contractors with freedom in design, construction methods, materials, and innovation in performing the contract as long as the standard specified is fulfilled. While PBMC implementation is increasing around the world, it can be considered new in Malaysia. This research aims to investigate the viability and practicability of PBMC's implementation for road maintenance in Malaysia. Specifically, the research's objective is to identify factors that are affecting the adoption of PBMC for road maintenance works in Malaysia. To achieve that objective, interview data from industry practitioners that are involved in managing roads are analyzed. Factors affecting PBMC's implementation for road maintenance in Malaysia can be categorized into two groups: PBMC (ex. awareness on PBMC) and Non-PBMC (ex. contractor's integrity) related factors. The findings of this research would help policymakers, industry practitioners, and researchers improve the success of implementing PBMC in the facility management industry.